Ambulatory blood pressure monitoring in healthy children with parental hypertension - TOPUZOĞLU, AHMET; ALPAY, HARİKA (SPRINGER, 2009)
The aim of this study was to compare ambulatory blood pressure monitoring (ABPM) parameters in offspring with at least one hypertensive parent (HP) to offspring with normotensive parents (NP) and to determine whether gender of parent or child might influence the association between parental hypertension and blood pressure (BP). Eighty-nine healthy children (mean age 11.1 +/- 3.9 years) with HP and 90 controls (mean age 10.5 +/- 3.1 years) with NP were recruited. Age, gender, and height did not differ between the two groups, whereas children of HP had higher weight, body mass index (BMI), and waist circumference compared with healthy controls. No difference was found in casual BP between the two groups. In contrast, during ABPM daytime and nighttime mean systolic and diastolic BP and mean arterial pressure (MAP) standard deviation scores (SDS) were significantly elevated in children with HP. The mean percentage of nocturnal BP decline (dipping) was not significantly different between the two groups. Children with hypertensive mothers had higher daytime systolic and MAP SDS than controls; no such difference was detected for children with hypertensive fathers. Daytime systolic and MAP SDS were significantly elevated in boys with HP compared with boys with NP but failed to be significant in girls. Multiple linear regression analysis showed that parental history of hypertension (B=0.29) and BMI (B=0.03) were independently correlated with increase of daytime MAP SDS. Early changes in ambulatory BP parameters were present in healthy children of HP. BP in HP offspring was influenced by the gender of the affected parent and the offspring.
Keywords: Ambulatory blood pressure; Family history; Hypertension; Blood pressure; FAMILY-HISTORY; MASS INDEX; FOLLOW-UP; CHILDHOOD; REPRODUCIBILITY; MORTALITY; AMERICAN; PROTEIN; ADULTS; GENES